Avaliação das pressões respiratórias máximas em crianças e adolescentes da grande Natal: elaboração de uma equação preditiva - Nunes, Thiago César Viana (2012)
The human respiratory system was so designed that would allow efficient ventilation, regardless of variations in the external environment that may hinder the act of breathing, such an act involves dozens of variables, among them we find the respiratory depression, which is nothing more than respiratory muscle strength. The pressures are widely used in several cases: Neuro-muscular; evolution of pulmonary dysfunction and a predictor for discontinuation of mechanical ventilation. Therefore it was proposed to carry out evaluations of these respiratory pressures for children and adolescents aged 10 to 16 years and propose a predictive equation that involves the anthropometric variables age (A, years), body mass (BM, kilograms) and height (H, meters) with maximal respiratory pressures (maximum inspiratory and expiratory pressure). Evaluations were performed in this age group of students in public and private schools of the Grande Natal , measurements were performed using the analogue manometer, were children and adolescents and their parents gave informed consent. 517 samples were taken, and 250 for males (M), 255 for females (F) and 12 were excluded according to our exclusion criteria. The sample was subdivided into three age groups (10-11, 12-13 and 14 to 16 years old). It was found through the student s t test (p ≤ 0.05) for all variables studied, children and male adolescents had higher means than females, except for the MC. For the correlation between the variables found significant correlation (p <0.05) among all the variables when analyzed as pairs except between MIP and height for females. The development of predictive equations (for p ≤ 0.05) based on three types of strategies adopted were restricted to two association between anthropometric variables isolated, resulting in: for males: MIP = -32.29 + (-2.11*A) + (-0.52*BM), MIP = 9.99 + (-0.36*BM) + (-49.40*H); MEP = 18.54 + 3.53*A + 0, 42*BM, MEP = -33.37 + 2.78*A + 52.18* H, MEP = -17.39 + 0.33*BM + 55.04*H; and, for females we find: MEP = 24.32 + 2.59 * A + 0.24*BM